The mathematical model of inner migration - Kanišauskas, Vaidotas (Lietuvos matematikos rinkinys, 2016)
The model of inner migration is applied when considering the percentage of inhabitants residing in administrative units of a state in different time units. Such data allows applying the polynomic distribution and test the statistical hypothesis suggesting that, in the time running, the amounts of inhabitants have cardinally changed in territorial unites of the state; and it was possible only due to inner migration.